1985
DOI: 10.1111/j.2042-7158.1985.tb04954.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iontophoresis and vehicle pH on the in-vitro permeation of lignocaine through human stratum corneum

Abstract: The effect of iontophoresis and the pH of aqueous vehicles on the rate and extent of permeation of lignocaine through excised human stratum corneum was investigated. In the absence of iontophoresis, the rate of penetration was greatest at the higher pH values where lignocaine exists mainly in the unionized form; iontophoresis was most effective at the lower pH values where lignocaine is mainly ionized. At pH 3.4, and 5.2, the flux increased during iontophoresis, by approximately 8.5 and 4 times, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…We employed lidocaine (LC, pK a ϭ7.9) 15) and ketoprofen (KP, pK a ϭ4.0) 16) as model basic and acidic drugs, respectively. The drugs were dissolved in buffer solutions with several pHs so that we could evaluate the effect of the sugar esters on the percutaneous permeation of ionized and unionized drug species.…”
mentioning
confidence: 99%
“…We employed lidocaine (LC, pK a ϭ7.9) 15) and ketoprofen (KP, pK a ϭ4.0) 16) as model basic and acidic drugs, respectively. The drugs were dissolved in buffer solutions with several pHs so that we could evaluate the effect of the sugar esters on the percutaneous permeation of ionized and unionized drug species.…”
mentioning
confidence: 99%
“…4) Moreover, changes in pH alter the ionization of organic compounds which exist in a pH-dependent equilibrium between their ionized and nonionized states. 5) Since an optimal iontophoretic effect requires maximal ionization, 6,7) effective drug transport must minimize pH changes in the drug-containing solution. In order to overcome these disadvantages, systems using a silver or silver-silver chloride electrode 8,9) or pulsed direct current 10) have been investigated.…”
mentioning
confidence: 99%
“…Studies have shown that the iontophoretic delivery of local anesthetics is dependent upon the pKa and pH of the solution. 37,38 In addition, studies have demonstrated that the iontophoretic delivery of local anesthetics does not depend upon the concentration of the solution. 36 From our study, it appears that this phenomenon also holds true for EP.…”
Section: Discussionmentioning
confidence: 99%